Give Yourself Goosebumps : Please Don't Feed the Vampire - Book 15 - Stine, R. L. (London : Scholastic, 2016)
Theyre baa-ack! Make way for the bestselling childrens series of all time! With a fresh new look, GOOSEBUMPS is set to scare a whole new generation of kids. So reader beware--youre in for a scare! A Goosebumps Choose Your Own Horror Adventure! This Halloween youre stuck with a lame costume called "vampire in a can": a cheesy vampire costume stuffed inside a can. But then you finds a strange packet of red goo inside that will turn anyone who swallows it into a vampire. Will you swallow it and turn that lame costume into the real thing? Or will your adorable poodle Fifi wind up with a bite thats worst than her bark?
Keywords: Vampires -- Juvenile fiction; Juvenile horror